Fiscal federalism in the Baltic countries: from Soviets to EU - Viktor Trasberg (European Regional Science Association (ERSA), 2004)
The Baltic countries' local governments have been functioned during the last decade in a permanently changing environment. Like other transition countries, they inherited from the past extremely centralized administrative system. Along with radical reforms, administrative system was decentralized and various functions were devolved from central to lower levels of government. Despite that, municipalities are still fiscally strongly dependent from central authorities. Often their fiscal capacity is not adequate to act in accordance with functions stipulated by laws. Many local governments' revenues from taxes and user-charges are insufficient to finance efficiently their expenditures. Disparities in municipalities' fiscal situation are correlated with unbalanced regional growth, social degradation in the low-income regions and growing differentiation by municipalities' residents on access to education and healthcare. Membership of the European Union brings new tasks and responsibilities for the Baltic local governments. Municipalities should increase their economic sustainability and enhance administrative capacity to explore EU accession funds and implement EU policies. Considering the above-mentioned problems, the paper focuses on current fiscal situation of local governments in the Baltic countries. The main interest is to analyze local municipalities' revenue level and structure, expenditure composition and fiscal autonomy conditions
Keywords: 330